Milwaukee County Small-to-Medium Photovoltaic Power Station Site Suitability - Thiewes, Robert; Swingen, Zachary; Smith, Matthew (My University, 2018)
Wisconsin currently generates roughly 50% of the state’s power from coal, while under 10% of energy generated comes from renewable resources. Solar energy is a globally-recognized source for responsible energy production based on its renewability and its potential to significantly lower carbon emissions. Our project aims to identify and rank any potential suitable sites for a small to medium sized solar power collection station in Milwaukee County, WI while taking into account economic, environmental, and technical conditions.
Inlcudes Maps, Figures, Tables, Appendices and Bibliography.
Keywords: Milwaukee; Milwaukee County; Site suitability; Photovoltaic power station; Solar power